Ultrastructure and histochemistry of the male reproductive system of the genus Callinectes Stimpson, 1860 (Brachyura: Portunidae) - Watanabe, Timoteo T. [UNESP]; Nascimento, Fabiana A. [UNESP]; Mantelatto, Fernando L.; Zara, Fernando J. [UNESP] (Wiley, 2020)
We described the ultrastructure and histochemistry of the reproductive system of five Callinectes species, and evaluate the seasonal variation in weight of the reproductive system and hepatopancreas by comparing annual changes of somatic indices. The somatic indices changed little throughout the year. In Callinectes, spermatogenesis occurs inside the lobular testes and, within each lobule, the cells are at the same developmental stage. Spermatogenesis and spermiogenesis follow the same development pattern in all Callinectes studied. Mature spermatozoa are released into the seminiferous ducts through the collecting ducts. Cells of the vas deferens are secretory as evidenced by rough endoplasmic reticulum, Golgi complex, and secretory vesicles that produce the seminal fluid. The anterior vas deferens shows two portions: proximal and distal. In proximal portion (AVDp), spermatozoa are clustered and embedded in an electron-dense, basophilic glycoproteinaceous secretion Type I. In the distal portion (AVDd), the spermatophore wall is formed by incorporation of a less electron-dense glycoproteinaceous secretion Type II. The secretion Type I change to an acid polysaccharide-rich matrix that separates the spermatophores from each other. The median vas deferens (MVD) stores the spermatophores and produces the granular glycoproteinaceous seminal fluid. The posterior vas deferens (PVD) has few spermatophores. Its epithelium has many mitochondria and the PVD seminal fluid changes into a liquid and homogeneous glycoprotein. Many outpocketings in the PVD and MVD help to increase the fluid production. Overall, the reproductive pattern of Callinectes is similar to other species that produce sperm plugs. The secretions of AVD, MVD, and PVD are responsible for the polymerization that forms the solid, waxy plug in the seminal receptacle. The traits identified here are common to all Portunidae species studied so far.
Keywords: blue crabs; electron microscopy; Portunoidea; sperm plug